Purification and physicochemical properties of a ribonuclease produced by Aspergillus flavipes (IZ : 1501) - Gomes, E.; Serzedello, A.; Da Silva, R. (Faculty Press, 1998)
A RNase of Aspergillus flavipes (IZ:1501) was purified from culture medium by chromatography on DEAE-cellulose and Sephadex G50 columns, after 96 h of cultivation. The molecular weight of the RNase was estimated to be 15 kD by gel filtration using Sephadex G100, and the optimum pH and temperature were 4.0 and 55 degrees C, respectively. Catalytic activity was inhibited by Hg2+, Ag+, Fe3+, Co2+ and Zn2+. The enzyme showed guanosine specificity producing only 3'-GMP from yeast RNA.
Keywords: ribonuclease; Aspergillus; nucleotides